Mechanical performance and corrosion behaviour of diffusion-bonded A5083 aluminium and A36 mild steel with gallium interlayer - Ismail, Asmawi; Othman, Nurul Husna; Mustapha, Mazli; Mohamed Saheed, Mohamed Shuaib; Abdullah, Zaki; Muhammed, Musa; Mohamed Saat, Asmalina; Mustapha, Faizal (Multidisciplinary Digital Publishing Institute, 2022)
This article investigated the mechanical performance and corrosion behaviour of a diffusion-bonded A5083 aluminium/A36 mild steel dissimilar joint with a Gallium (Ga) interlayer. The bonding parameters were the bonding temperature (525 and 550 °C), holding time (60 and 120 min) and surface roughness (800 and 1200 grit). Property characterisation was achieved using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX) analysis, Vickers microhardness tester, Izod impact tester and potentiodynamic polarisation testing. The results revealed that the significance of the bonding parameters was in the order bonding temperature > surface roughness > holding time. Increasing the bonding temperature resulted in an increase in the impact strength and a corresponding reduction in the corrosion rate and microhardness. However, increasing the grit size decreased the microhardness and a corresponding increase in the impact strength and corrosion rate. The impact strength and corrosion rate decreased with the increasing holding time while the microhardness followed a reverse trend. It was also discovered that incorporating the Ga interlayer resulted in a 67.9% improvement in the degradation rate.